Uwarunkowania technologiczne a funkcjonowanie zintegrowanego systemu zarządzania jakością w Zakładzie Produkcji Spożywczej RAG - Drozdowska, Agnieszka; Lesiów, Tomasz (Technological Aspects Versus Functioning of Integrated Quality Management System in Food Company RAG, 2007)
The aim of the paper is to present functioning of integrated quality management system and its connection with technological process of salty and sesame sticks in Food Company RAG. The integrated system introduced in the company comprises: GMP, GHP, HACCP, Quality Management System ISO 9001, and standard BRC. The authors present the benefits of integration of systems on the basis of BRC standard, especially concerning guarantee of product health safety, its high quality, improvements in quality management and better understanding and more effective work of persons responsible for the operations critical for technological quality. The workers opinion poll revealed that within 4 years, since HACCP implementation in the company, the attitude of the staff toward performed work, labour duties, atmosphere in the company and quality understanding has changed. The practical and continuous training of workers knowledge of the system principles and procedures is the key to get benefits from quality management integration and up-to-date technology of production and to offer the customer the product of the highest quality.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Technologia (12); 2007; nr 1172, s. 39-58